The development of the concept of Mahdism in The Malay Sunni world - Mohd Amin, Wan Mohd Azam (International Islamic University Malaysia, 2007)
This paper examines the development of the Malay concept of Mahdism (Messiah) and the reasons behind it. It is believed that this concept seeped into the Malay Muslim mind along with the advent of Islam to this region. Many personalities and groups in Malaysia subscribed to this concept including the Darul Arqam group which had already determined its own Malay Mahdi. By making an analytical evaluation on their written and recorded materials, as well as those of others, it is suggested that the misuse of Aristotelian syllogism in the methodology of reasoning and some influences of Sji'ism led Darul Arqam to uphold doctrines deviating from that of the Malay Muslim majority in Malaysia. For this reasons, the Darul Arqam group and its activities were banned by the Malaysian government.